A Drug–Drug Interaction Study of a Novel Selective Urate Reabsorption Inhibitor, SHR4640, and Xanthine Oxidase Inhibitor, Febuxostat, in Patients With Primary Hyperuricemia. (20th October 2022) - Wang, Chenjing; Yu, Qing; Jiang, Xin; Deng, Yujie; Sun, Feifei; Li, Xin; Tao, Ye; Lin, Pingping; Ma, Yaping; Zhu, Yuxian; Li, Chengqian; Cao, Yu
Abstract: SHR4640 is a novel, selective urate reabsorption inhibitor. As the mode of action of SHR4640 differs from that of a xanthine oxidase inhibitor, such as febuxostat, coadministration of these drugs may be a treatment option for patients with primary hyperuricemia. We assessed the potential drug–drug interaction between SHR4640 and febuxostat. In this single‐center, open‐label, randomized, drug–drug interaction study, subjects received 80 mg febuxostat or 10 mg SHR4640 alone daily in the first week, whereas during the second week a combination of SHR4640 and febuxostat was administered daily to all subjects. Plasma concentrations of SHR4640 and febuxostat were analyzed. We compared their pharmacokinetic and pharmacodynamic parameters and assessed both safety and tolerability. Compared with febuxostat alone, the geometric mean ratios (90%CIs) of the maximum concentration (Cmax ) and the area under the plasma concentration–time curve over the dosing interval τ (AUC0–τ ) for febuxostat after coadministration were 1.284 (1.016 to 1.621) and 0.984 (0.876 to 1.106), respectively. The geometric mean ratios (90%CIs) of Cmax and AUC0–τ for SHR4640 after coadministration compared with SHR4640 alone were 0.910 (0.839 to 0.988) and 0.929 (0.893 to 0.966), respectively. Febuxostat had no effect on SHR4640 pharmacokinetic parameters, as the 90%CIs of the geometric mean ratios were all within the range of 0.80 to 1.25. The coadministration of febuxostat and SHR4640 was well tolerated. The coadministration of SHR4640 with febuxostat was not associated with any clinically relevant pharmacokinetic drug interactions. SHR4640 combined with febuxostat had a synergistic effect on reducing uric acid in the pharmacodynamics, with the AUC decreasing from 7440 to 3170 h μmol/L compared with febuxostat alone and from 5730 to 2960 h μmol/L compared with SHR4640 alone.